2017
DOI: 10.1515/slgr-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Using Memrise in Legal English Teaching

Abstract: Abstract.Memrise is an educational tool available both online and for mobile devices. Memrise uses flashcards and mnemonic techniques to aid in teaching foreign languages and memorizing information from other subjects, e.g. geography, law or mathematics. Memrise courses are created by its users through the process of crowdsourcing; therefore they are tailored to the individual needs of the users and may focus on the specific content of a particular coursebook or classes.The paper will attempt to present possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Memrise [65] 3D Anatomical App [56] Mobile English Learn English on the go [43] Google Translate [55] Mobile dictionary SPEARA [62] Books vs. Brains@PolyU [60] Reading app Reading Practice App [64] Read with QR codes [67] Digital textbooks [47]…”
Section: Type Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Memrise [65] 3D Anatomical App [56] Mobile English Learn English on the go [43] Google Translate [55] Mobile dictionary SPEARA [62] Books vs. Brains@PolyU [60] Reading app Reading Practice App [64] Read with QR codes [67] Digital textbooks [47]…”
Section: Type Examplesmentioning
confidence: 99%
“…Vocabulary is one of the skills focused on in mobile learning. Studies conducted to identify learners' perception towards using mobile learning in improving their vocabulary acquisition reported positive perceptions [43,56,62,65]. Other studies said mobile learning helped learners acquire more vocabulary, and showed that specific discipline apps expanded their vocabulary [55,60].…”
Section: Rq2: What Are the Language Skills Focused On Mobile Learning For Esp?mentioning
confidence: 99%
“…The spaced repetition technique based on the theory that a proper time interval of information representation allows maximizing the rate of learning [29]. AI technology in spaced repetition software applications allows recording and tracking progress, when the information was presented, how effective it was for a particular learner, and then to adapt the time intervals of the information representation when it is most appropriate for the learner.…”
Section: Using Ai To Reduce Educational Inequalitymentioning
confidence: 99%
“…This issue could be solved in two ways: either making raw speech data available for developers to use external voice recognition tools such as Google's Cloud Speech-to-Text (SST) API 8 (which would also enable additional features such as using confidence scores for pronunciation training), or by integrating multilingual ASR within the Alexa development environment. Including multilingual functionality in this way would also allow users to create their own flashcards to learn and practice, which has been shown to be a positive feature of flashcard software that increases student performance [6,20].…”
Section: Research Question Threementioning
confidence: 99%